Diagnosing the decline of the Greenland White-fronted Goose Anser albifrons flavirostris using population and individual level techniques - Weegman, Mitch D.; Fox, Anthony D.; Hilton, Geoff M.; Hodgson, David J.; Walsh, Alyn J.; Griffin, Larry R.; Bearhop, Stuart (Wildfowl, 2017)
Following an increase in numbers from 1982 to 1998, the Greenland White-fronted Goose Anser albifrons flavirostrisdeclined over the period 1999â€“2015, stimulating detailed analyses at the population and individual level to provide a better understanding of the dynamics of this subspecies. Here we synthesise the results of the analyses in order to describe the potential reasons for the decline. Utilising a 27-year capture-mark-recapture dataset from the main wintering site for these birds (Wexford, Ireland), multistate models estimated sex-specific survival and movement probabilities. Our results suggested no evidence of a sex bias in emigration or â€œremigrationâ€ rates. These analyses formed the foundation for an integrated population model (IPM), which included population size and productivity data to assess source-sink dynamics of Wexford birds through estimation of age-, site-, and year-specific survival and movement probabilities. Results from the IPM suggested that Wexford is a large sink, and that a reduction in productivity is an important demographic mechanism underlying population change for birds wintering at the site. Low productivity may be due to environmental conditions in the breeding range, because birds bred successfully at youngest ages when conditions in Greenland were favourable in the year(s) during adulthood prior to and including the year of successful breeding. This effect could be mediated by prolonged parent-offspring relationships, as birds remained with parents into adulthood, forfeiting immediate reproductive success despite there being no fitness benefits to offspring of family associations after age 3 years. Global Positioning System and acceleration data collected from 15 male individuals suggested that two successful breeding birds were the only tagged individuals whose mate exhibited prolonged incubation. More data is required, however, to determine whether poor productivity is attributable to deferral of nesting or to failure of nesting attempts. Spring foraging did not appear to limit breeding or migration distance because breeding and non-breeding or failed-breeding birds, as well as Irish and Scottish birds, did not differ in their proportion of time spent feeding or on energy expenditure in spring. We recommend that future research should quantify the demography of other Greenland White-fronted Goose wintering flocks, to assess holistically the mechanisms underlying the global population decline.